As relações étnico-raciais em foco: o ensino de leitura do artigo de opinião como instrumento de empoderamento discursivo para transformação social - Silva, Queite Diniz dos Santos da (2024)
This research presents a study on ethnic-racial relations due to the recurrent episodes of prejudice, discrimination, racial injury and racism in social spaces, assuming that school is the second main agent of socialization and therefore, it cannot be alien to this discussion, considering that, after the family, it is in the educational environment that critical and active citizens are trained. Thus, this research is part of experiences observed, experienced and evaluated in the personal, professional and social sphere. And aims to teach reading, in the critical-discursive perspective, having as support the discursive genre article of opinion focused on the reflection of ethnic-racial relations, to contribute to the expansion of knowledge, argumentation, discursive empowerment for social transformation. The research is based on the assumptions of Law 10.639/03, which makes compulsory the teaching on History and AfroBrazilian Culture and Law 12.288/10 of the Statute of Racial Equality, which presents a set of affirmative actions, reparatory and compensatory measures that seek to guarantee fundamental rights to the black population of Brazil, and is also aligned with the ideas of Almeida (2021); Bento (2022); Gomes (2013, 2017); Munanga (2005, 2009, 2023); Ramos (2017); Ribeiro (2019) and Silva (2007, 2012, 2015). The fractions that refer to the development of incentive to reading will be based on Brandão (2004); Bonifácio (2015); Koch and Elias (2010); Orlandi (2012) and Solé (1998). The study of gender, in turn, will be based on Bakhtin (2011) and Marcuschi (2008). Therefore, it is action research of qualitative approach and interventionist character, based on the theory of Discourse Analysis in the critical-discursive perspective. The procedures and instruments used to obtain data were participant observation, socio-historical questionnaire, diagnostic evaluation, workshops implemented in a class of elementary school flow correction Project Crossing. After the analysis of pedagogical intervention, carried out through the workshops, it was found that the teaching of reading provided students with more desenvolta reading, more reflective and critical, better literate racially, with greater discursive empowerment and aware of their racial identity to intervene with the anti-racist perspective. In addition to these results, a pedagogical notebook was produced with the intention of helping teachers in the implementation of the law 10.639/03.